Microstructure and Mechanical Properties of Recycled Aggregate Concrete in Seawater Environment - Pengjun Yue; Zhuoying Tan; Zhiying Guo (The Scientific World Journal)
This study aims to conduct research about the microstructure and basic properties of recycled aggregate concrete under seawater corrosion. Concrete specimens were fabricated and tested with different replacement percentages of 0%, 30%, and 60% after immersing in seawater for 4, 8, 12, and 16 months, respectively. The basic properties of recycled aggregate concrete (RAC) including the compressive strength, the elastic modulus, and chloride penetration depth were explicitly investigated. And the microstructure of recycled concrete aggregate (RCA) was revealed to find the seawater corrosion by using scanning electron microscope (SEM). The results showed that higher amount of the RCA means more porosity and less strength, which could lower both the compressive strength and resistance to chloride penetration. This research could be a guide in theoretical and numerical analysis for the design of RAC structures.